2015
DOI: 10.1002/pra2.2015.145052010043
|View full text |Cite
|
Sign up to set email alerts
|

Online privacy and informed consent: The dilemma of information asymmetry

Abstract: Every day billions of users allow cloud-based internet services to collect, store, and manage their personal information. The use of this information is constrained only by long, wordy privacy agreements that users likely did not read before clicking "Agree." Even if they were to read them, would users understand these policies? We present the results of a two-part privacy survey that assessed users' knowledge and opinions of online privacy issues. We asked users not only what they think, but what they know. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
(12 reference statements)
0
28
0
Order By: Relevance
“…The practical option, for qualitative researchers and online, is to make information available to people, so that the material can be read and absorbed at a pace that suits the individual. In practice, it is often the case that signed consent forms have not been read and, even if they have, recollecting what has been signed is problematic [3,50].…”
Section: Reflexivitymentioning
confidence: 99%
See 3 more Smart Citations
“…The practical option, for qualitative researchers and online, is to make information available to people, so that the material can be read and absorbed at a pace that suits the individual. In practice, it is often the case that signed consent forms have not been read and, even if they have, recollecting what has been signed is problematic [3,50].…”
Section: Reflexivitymentioning
confidence: 99%
“…Proposing that consent to the collection and retention of personal data be meaningful and fair has been posited as a way forward [3,60]. Building on the Fair Transaction model of consent [60], [54], argue that a strengthening of informed consent from a legal perspective could result in undermining the effectiveness of the consent mechanism itself, and thereby have a detrimental effect on trust in data processing and privacy protection.…”
Section: Reflexivitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the Jensen et al study, they found that concern was reduced by the mere presence of privacy policies, even if they were not read [36]. Policies are frequently written in such an obfuscated fashion that even users who care about their privacy might have little recognition of the data they are disclosing [51]. Acceptance is gradually becoming more implicit, moving from click-wrap licensing through checking a box, to browse-wrap licensing by reading a webpage [52].…”
Section: E Policies and Configurationsmentioning
confidence: 99%